Effects of different foot progression angles and platform settings on postural stability and fall risk in healthy and medial knee osteoarthritic adults - Khan, Saad Jawaid; Khan, Soobia Saad; Usman, Juliana; Mokhtar, Abdul Halim; Abu Osman, Noor Azuan (SAGE Publications, 2018)
This study aims to investigate the effects of varying toe angles at different platform settings on Overall Stability Index of postural stability and fall risk using Biodex Balance System in healthy participants and medial knee osteoarthritis patients. Biodex Balance System was employed to measure postural stability and fall risk at different foot progression angles (ranging from −20° to 40°, with 10° increments) on 20 healthy (control group) and 20 knee osteoarthritis patients (osteoarthritis group) randomly (age: 59.50 ± 7.33 years and 61.50 ± 8.63 years; body mass: 69.95 ± 9.86 kg and 70.45 ± 8.80 kg). Platform settings used were (1) static, (2) postural stability dynamic level 8 (PS8), (3) fall risk levels 12 to 8 (FR12) and (4) fall risk levels 8 to 2 (FR8). Data from the tests were analysed using three-way mixed repeated measures analysis of variance. The participant group, platform settings and toe angles all had a significant main effect on balance (p ≤ 0.02). Platform settings had a significant interaction effect with participant group F(3, 144) = 6.97, p < 0.01 and toe angles F(21, 798) = 2.83, p < 0.01. Non-significant interactions were found for group × toe angles, F(7, 266) = 0.89, p = 0.50, and for group × toe angles × settings, F(21, 798) = 1.07, p = 0.36. The medial knee osteoarthritis group has a poorer postural stability and increased fall risk as compared to the healthy group. Changing platform settings has a more pronounced effect on balance in knee osteoarthritis group than in healthy participants. Changing toe angles produced similar effects in both the participant groups, with decreased stability and increased fall risk at extreme toe-in and toe-out angles.